Development and benchmarking of numerical model in OpenFOAM® for the prediction of channel segregation during columnar alloy solidification. (1st October 2022) - Kumar, Alok; Singh, Anup; Kumar, Arvind
Highlights: Benchmark sn-5 wt%Pb alloy solidification problem is simulated using OpenFOAM solver. Mesh sensitivity analysis is performed to resolve the flow in channels segregates. Effect of microsegregation and mushy zone models on channels formation is studied. Scheil's model predicts more negative and positive segregation than Lever rule. Inertial drag in mushy zone significantly affects the channel segregates formation. Abstract: In the past, most of the numerical studies on the prediction of macrosegregation and mesosegregation (e.g. channel type segregation) were performed using in-house codes and commercial software, both of which have limitations such as huge license costs, non-availability for general public research etc. In this study, a dedicated CFD solver is developed in an open-source platform – OpenFOAM® for the prediction and characterization of channel segregates in castings. The solver accounts for the fluid flow, heat transfer, species transport, multiscale segregation, solidification and mushy zone drag phenomena that occur during alloy solidification. The developed solver is extensively validated with the reported benchmarked experimental and numerical results for the sn-Pb alloy solidification. Direct numerical simulations (DNS) are performed to resolve the flow field in and around the channels (which are of mesoscopic length scale) for the first time. It is observed that mesh size ≤ 2 d 2 (secondary dendritic arm spacing) is required to resolve the flow in channels and accurately predict their morphology and locations. Further, the effect of different microsegregation and mushy zone drag models on the segregation and morphology of channel segregates is thoroughly investigated. The predicted extent of negative and positive segregation is found to be more (negative segregation ∼ 7.7 wt%Pb and positive segregation ∼ 18.7 wt%Pb) in Scheil's microsegregation model compared to Lever rule. Furthermore, the inertial drag in the mushy zone significantly affects the convective transport of solute and thereby the morphology and the number of channel segregates.